The impact of a change in the national minimum wage on the distribution of hourly wages and household income in Ireland - Paul Redmond; Karina Doorley; Séamus McGuinness (The Economic and Social Research Institute (ESRI), 2019)
This ESRI study, funded by the Low Pay Commission, found that the 2016 increase in the Irish minimum wage reduced hourly wage inequality between high and low earners by up to 8 per cent. However, there was no strong impact on the income of households.
Keywords: 330